2017
DOI: 10.1590/0074-02760160355
|View full text |Cite
|
Sign up to set email alerts
|

The use of circulating cathodic antigen rapid test and serology for diagnosis of active Schistosoma mansoni infection in migrants in Italy, a non-endemic country: a cross sectional study

Abstract: Diagnosis of schistosomiasis in migrants coming from endemic areas can be difficult, especially in asymptomatic subjects. Light-intensity disease, in fact, may be missed due to the low sensitivity of the stool microscopy and serologic testing cannot distinguish between a resolved infection and an active infection in patients who have been infected and treated in the past, because specific antibodies can persist despite cure. We describe a cross-sectional study conducted on 82 migrants tested for Schistosoma ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Another strength was the use of POC-CCA, a commercialized urine-based antigen test that is used specifically for the detection of active S . mansoni infection in humans [64]. The use of POC-CCA enabled the large, nationwide scale of the study with its ease of use under field conditions and minimal training requirements for its application [65].…”
Section: Discussionmentioning
confidence: 99%
“…Another strength was the use of POC-CCA, a commercialized urine-based antigen test that is used specifically for the detection of active S . mansoni infection in humans [64]. The use of POC-CCA enabled the large, nationwide scale of the study with its ease of use under field conditions and minimal training requirements for its application [65].…”
Section: Discussionmentioning
confidence: 99%
“…Previous screening studies conducted on migrant populations in Europe found a questionably low prevalence of schistosomiasis, probably depending on the diagnostic tools used [ 19 , 21 , 23 25 ]. Indeed, only about 40% of our patients included in the endemic group had a diagnosis of confirmed schistosomiasis, and therefore, had we relied on ova identification only, the number of cases diagnosed would have been much lower.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Recent studies among African migrants in Europe conjectured that the POC-CCA urine cassette test might also be considered for individual diagnosis. 21 23 …”
Section: Discussionmentioning
confidence: 99%